Pengaruh Green Product Innovation Dan Green Price Terhadap Sustainable Consumption Melalui Lifestyle Gen Z Sebagai Variabel Moderasi Pada Konsumen The Body Shop Di Kota Malang - Maharani, Puteri Aurelia; Rizal, Mohammad; Normaladewi, Andi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study was conducted to analyze the influence of green product innovation and green price on sustainable consumption, with Gen Z lifestyle as a moderating variable. The research was carried out on consumers of The Body Shop products in Malang City using a quantitative approach. The sample consisted of 75 respondents selected through proportional sampling techniques. Data analysis was performed using SmartPLS version 4.1.1.3. The results showed that green product innovation had a significant effect on sustainable consumption, and green price also had a significant effect on sustainable consumption. The moderation test indicated that the Gen Z lifestyle negatively moderates the relationship between green product innovation and sustainable consumption, and positively moderates the relationship between green price and sustainable consumption. Keywords: Green Product Innovation, Green Price, Sustainable Consumption, Gen Z Lifestyle.